1997
DOI: 10.1159/000127203
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of Gonadotropin-Releasing Hormone-lmmunoreactive Terminal Nerve Cells: Effects on the Reproductive Behavior of Male Dwarf Gouramis

Abstract: Functions of the terminal nerve (TN) are largely unknown. To examine whether gonadotropin-releasing hormone (GnRH)-immunoreactive TN cells (TN-GnRH cells) are involved in the control of reproductive behavior, effects of lesions of TN-GnRH cells were studied in male dwarf gouramis, Colisa Mia. After bilateral electrolytic lesion, a characteristic impairment was observed in one of the repertoires of male reproductive behavior, nest-building. The occurrence of mating trials in which males showed no nest-building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(106 citation statements)
references
References 30 publications
5
101
0
Order By: Relevance
“…The correlation between GnRH1 and GnRH3 with sexual behavior and nest-building was previously reported for blue gourami and other fish [44,45]. Thus, it is suggested that in non-reproductively active males, an increase in water salinity and conductivity induces GnRH1gene expression, which in turn increases GtH and PRL synthesis.…”
Section: Discussionsupporting
confidence: 58%
“…The correlation between GnRH1 and GnRH3 with sexual behavior and nest-building was previously reported for blue gourami and other fish [44,45]. Thus, it is suggested that in non-reproductively active males, an increase in water salinity and conductivity induces GnRH1gene expression, which in turn increases GtH and PRL synthesis.…”
Section: Discussionsupporting
confidence: 58%
“…The TN-GnRH system has been suggested to affect the motivational or arousal state of the animal (Oka and Matsushima, 1993;Yamamoto et al, 1997;Abe and Oka, 2007). If GnRH enhances odorant contrast in general, a motivated animal can respond more appropriately to the external environment.…”
Section: What Is the Function Of Gnrh In The Olfactory System?mentioning
confidence: 99%
“…Recently, Yamamoto et al (1997) reported that lesioning the terminal nerve GnRH neurons changes the threshold for nest-building behavior in the dwarf gourami (Colisa lalia), but does not influence other reproductive behaviors. Their data imply that 5Trp 7 Leu 8 6GnRH may indeed be related to reproductive motivation.…”
Section: Fig 2 Expression Of the Threementioning
confidence: 99%